2011
DOI: 10.1002/jwmg.88
|View full text |Cite
|
Sign up to set email alerts
|

Decision analysis for conservation breeding: Maximizing production for reintroduction of whooping cranes

Abstract: Captive breeding is key to management of severely endangered species, but maximizing captive production can be challenging because of poor knowledge of species breeding biology and the complexity of evaluating different management options. In the face of uncertainty and complexity, decision‐analytic approaches can be used to identify optimal management options for maximizing captive production. Building decision‐analytic models requires iterations of model conception, data analysis, model building and evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…In brown kiwis, risk of hatching failure was high if artificial incubation began before the second half of incubation but then leveled off (Robertson et al, 2006). Similarly, a study on whooping cranes found that 16 days of parental incubation (of a 30 day incubation period) provided the most productive trade-off between egg production and hatching success (Smith et al, 2011), but that hatching probability continued to increase if eggs were naturally incubated throughout the entire incubation period. We found a steep linear increase in the proportion of eggs hatched with parental incubation time (F 1,10 = 57.1, R 2 = 0.87, b = 0.05, p < 0.001) which did not level off.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In brown kiwis, risk of hatching failure was high if artificial incubation began before the second half of incubation but then leveled off (Robertson et al, 2006). Similarly, a study on whooping cranes found that 16 days of parental incubation (of a 30 day incubation period) provided the most productive trade-off between egg production and hatching success (Smith et al, 2011), but that hatching probability continued to increase if eggs were naturally incubated throughout the entire incubation period. We found a steep linear increase in the proportion of eggs hatched with parental incubation time (F 1,10 = 57.1, R 2 = 0.87, b = 0.05, p < 0.001) which did not level off.…”
Section: Discussionmentioning
confidence: 98%
“…Since little is known about the factors that cause hatching failure in captive bird populations (Smith et al, 2011) and since offspring survival can be an important limitation on the contribution of captive populations to ex situ conservation efforts, our study is not only of importance to the conservation of 'alala, but may also be of value to the captive management of other species.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given these caveats, an ex situ propagation strategy may be a potential solution (e.g. whooping crane, Grus americana ; [75]).…”
Section: Discussionmentioning
confidence: 99%
“…We used the estimated w k to calculate the Bayes’ factor (BF) for each covariate, where the BF represents the odds ratio of inclusion (Smith et al . ). Following the recommendations of Link and Barker (, p. 2632) and the example of Converse et al .…”
Section: Methodsmentioning
confidence: 97%